Measurement and Analysis of Crowdsourced Vehicle Vibration Levels during Last Mile Delivery Segments for Parcel Shipments - Kyle Dunno; Purushottam Chavan (Vibration, 2022)
Crowdsourced logistics has emerged as a delivery channel for many single-parcel packages. As a result, this logistics network has introduced personal passenger vehicles as a means to transport parcels during last mile delivery segments. To understand this network’s vibration levels and cargo capacity restraints, four vehicle types (a sedan, sports sedan, compact SUV and full-size SUV) commonly used in crowdsourced logistics deliveries were selected for measurement and analysis. This study shows that the vibration levels were significantly higher in the vertical axis and that the overall vibration energy increased as vehicle speed increased, except in the sedan. The sedan and SUV vehicles showed power spectral density peak frequencies in the low-frequency range, occurring at approximately 2 Hz, matching previous studies using similar vehicles. The vibration levels were greatest in the sports sedan and lowest in the sedan. The recorded vibration events showed a right-skewed heavy-tailed distribution and were non-Gaussian.